Stochastic Flow and Noise Associated with the Tanaka Stochastic Differential Equation - Watanabe, S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study the properties of the noise (in the Tsirelson sense) that is generated by the solutions of the well-known Tanaka equation.